2009
DOI: 10.1897/08-627.1
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis in zebrafish embryos: A potential approach to predict effect concentrations in the fish early life stage test

Abstract: Based on the hypothesis that analysis of gene expression could be used to predict chronic fish toxicity, the zebrafish (Danio rerio) embryo test (DarT), developed as a replacement method for the acute fish test, was expanded to a gene expression D. rerio embryo test (Gene-DarT). The effects of 14 substances on lethal and sublethal endpoints of the DarT and on expression of potential marker genes were investigated: the aryl hydrocarbon receptor 2, cytochrome P450 1A (cypla), heat shock protein 70, fizzy-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 24 publications
(42 reference statements)
1
21
0
2
Order By: Relevance
“…Analysis of embryos exposed to 3,4-dichloroaniline by microarrays and RT-PCR of selected candidate genes revealed changes in genes primarily involved in biotransformation and stress response (Voelker et al 2007). The identified genes-for instance cyp1a, hmox1-were also induced by 13 further test compounds (Weil et al 2008). A bar code-like response was observed in zebrafish exposed to 11 different chemicals (Yang et al 2007).…”
Section: Toxicodynamicsmentioning
confidence: 95%
See 1 more Smart Citation
“…Analysis of embryos exposed to 3,4-dichloroaniline by microarrays and RT-PCR of selected candidate genes revealed changes in genes primarily involved in biotransformation and stress response (Voelker et al 2007). The identified genes-for instance cyp1a, hmox1-were also induced by 13 further test compounds (Weil et al 2008). A bar code-like response was observed in zebrafish exposed to 11 different chemicals (Yang et al 2007).…”
Section: Toxicodynamicsmentioning
confidence: 95%
“…The molecular markers may respond more sensitively than endpoints of the conventional embryo test and might be used to predict chronic toxicity. The project Gene-DarT (gene expression D. rerio embryo test) aims at the identification of such sensitive marker genes and it has indeed been found that certain gene responses in the zebrafish embryo are exerted in the same range of concentration as toxic responses in a chronic fish toxicity test (fish early life stage test, Voelker et al 2007;Weil et al 2008). By inclusion of additional marker genes into GeneDarT, such as identified by Yang et al (2007) may be possible to correlate gene responses with chronic toxicity and to establish a prediction model.…”
Section: Prediction Of Adverse and Long-term Effectsmentioning
confidence: 99%
“…(Weil et al 2009;Hsu et al 2010) after exposure of fish embryos to Cd. However, little is known about the effects of Cd store in the sediment at a molecular level in fish early life stages (ELS) and the possible link between gene transcription disturbances and phenotypic impairments.…”
Section: Responsible Editor: Thomas Braunbeckmentioning
confidence: 99%
“…After 3, 8, 24, 32, and 48 h, lethal and sublethal effects (edemas, deformations, lack of spontaneous movement) were evaluated as described in Weil et al (2009) and dead embryos were removed. Oxygen content, pH and temperature were measured in all test vessels at the beginning (0 h) and end of the exposure (48 h).…”
Section: Fish Embryo Toxicity Testmentioning
confidence: 99%